Insights Gained From Zebrafish Models for the Ciliopathy Joubert Syndrome - Rusterholz, Tamara D. S.; Hofmann, Claudia; Bachmann-Gagescu, Ruxandra (Frontiers in Genetics, 2022)
Cilia are quasi-ubiquitous microtubule-based sensory organelles, which play vital roles in signal transduction during development and cell homeostasis. Dysfunction of cilia leads to a group of Mendelian disorders called ciliopathies, divided into different diagnoses according to clinical phenotype constellation and genetic causes. Joubert syndrome (JBTS) is a prototypical ciliopathy defined by a diagnostic cerebellar and brain stem malformation termed the “Molar Tooth Sign” (MTS), in addition to which patients display variable combinations of typical ciliopathy phenotypes such as retinal dystrophy, fibrocystic renal disease, polydactyly or skeletal dystrophy. Like most ciliopathies, JBTS is genetically highly heterogeneous with ~40 associated genes. Zebrafish are widely used to model ciliopathies given the high conservation of ciliary genes and the variety of specialized cilia types similar to humans. In this review, we compare different existing JBTS zebrafish models with each other and describe their contributions to our understanding of JBTS pathomechanism. We find that retinal dystrophy, which is the most investigated ciliopathy phenotype in zebrafish ciliopathy models, is caused by distinct mechanisms according to the affected gene. Beyond this, differences in phenotypes in other organs observed between different JBTS-mutant models suggest tissue-specific roles for proteins implicated in JBTS. Unfortunately, the lack of systematic assessment of ciliopathy phenotypes in the mutants described in the literature currently limits the conclusions that can be drawn from these comparisons. In the future, the numerous existing JBTS zebrafish models represent a valuable resource that can be leveraged in order to gain further insights into ciliary function, pathomechanisms underlying ciliopathy phenotypes and to develop treatment strategies using small molecules.